Strategi Komisi Pemilihan Umum Bojonegoro Dalam Meningkatkan Partisipasi Politik Generasi Z Pada Pilkada 2024 - Lenita Angraini; Esa Septian; Junadi (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Riau, 2026)
The research was conduducted due to the low political participation of Generation Z in the 2024 Regional Electins in Bojonegoro Regency, despite this group being the largest voter base. This study aims to analyze the strategy of the Bojonegoro General Elections Comminisiion (KPU) in increasing Generation Z participation in the 2024 Regional Elections. The research used a qualitative method with e case a study approach. Informants were selected through purposive sampling and included KPU Commisioners, university student, and students who participated in outhreach activites. Data were colleted trough interviews, observations, literature studies, and documention., then analyzed using SWOT analysis techniques. The results indicate that the Bojonegoro KPU’s strategy involes institutional synergy, social media optimization, and collaboration with educational institutions. This strategy is effective in increasing Generation Z involvement as voters and adhoc election organizers. The use of digital techology approach are key factor in fostering political awareness among the younger generation.